Ecotourism increases the field metabolic rate of whitetip reef sharks. (July 2016) - Barnett, Adam; Payne, Nicholas L.; Semmens, Jayson M.; Fitzpatrick, Richard
Abstract: Wildlife tourism has been shown to cause behavioural changes to numerous species. Yet, there is still little understanding if behavioural changes have consequences for health and fitness. The current study combined accelerometry and respirometry to show that provisioning whitetip reef sharks ( Triaenodon obesus ) for tourism increases their daily energy expenditure by elevating activity levels during periods when they normally rest. Field metabolic rate increased by 6.37% on provisioning days compared to non-provisioning days. Since metabolism is a key parameter influencing most biological and ecological processes, this represents some of the clearest evidence to date that ecotourism can impact critical biological functions in wild animals. Highlights: Little is known about consequences of wildlife tourism on animal health. Provisioning whitetip reef sharks increases their daily energy expenditure. Metabolic rate increased by 6.37% on provisioning compared to non-provisioning days. This is evidence that tourism can impact critical biological function in wild animals.